UPAYA MENINGKATKAN MOTIVASI DAN MINAT BELAJAR MELALUI WEBSITE MULTIMEDIA PEMBELAJARAN INTERAKTIF - Fauzi, Yusuf Zaki Nur; Innayah, Tessari; Tisnasari, Listika Yusi (Universitas Sultan Ageng Tirtayasa, 2024)
This ponder points to Extend Inspiration and Intrigued in Learning Through Intuitively Mixed media Learning Websites of Review IV Understudies of Al-Irsyad Al-Islamiyah 01 Purwokerto Rudimentary School. The subjects of this ponder were 28 review IV students. This research demonstrate could be a classroom activity investigate (PTK) with 4 stages of usage, to be specific, arranging, usage, perception and reflection. Information collection instruments and disobedient comprise of tests, surveys, perceptions and documentation. Agreeing to the comes about of the inquire about that has been done, the analyst concluded the taking after things, the inspiration of understudies to memorize expanded through the implementation of intelligently interactive media websites in Indonesian dialect learning, based on the comes about of the primary cycle of inquire about, the completeness of understudy learning come to 57%, at that point expanded to 89% in cycle II. Learning results are one of the pointers to decide the interface and inspiration of understudies to memorize, so that through interactive media websites can increment the interface and inspiration of understudies. Keywords: Media, Multimedia Website, Innovative, Interest, Motivation